Competition Law for the Asia-Pacific Economic Cooperation Community: Designing Shoes for Many Sizes - John Owen Haley (Washington University Global Studies Law Review, 2002)
The articles of this inaugural volume of the Washington University Global Studies Law Review initially were presented at two related conferences on competition law within the Asia-Pacific Economic Cooperation (APEC) community. The first conference was held in Victoria, British Columbia, in September 2000; the second, in Tokyo, Japan, in July 2001. Both were sponsored jointly by the Chuo University Institute of Comparative Law in Japan, the University of Victoria Centre for Asia-Pacific Initiatives in Canada, the Asian Law Center of the University of Washington in Seattle, and the Whitney R. Harris Institute for Global Legal Studies of Washington University in St. Louis. Neither conference would have been possible without the generous support of the Center for Global Partnership of the Japan Foundation. The aims of the project were twofold. We sought first to evaluate the current status of competition legislation in selected countries within the APEC community. At both meetings, the participants thus reviewed several of the most recent efforts to create effective regimes to promote competition policy within the APEC community. We considered what were, in effect, national reports on recent legislation in Indonesia and Thailand and the prospects for similar legislation in the People’s Republic of China. A second and more ambitious objective was to attempt an evaluation of both the most established competition law regimes in East Asia and a cluster of current issues. Thus, the discussions included critiques of competition policy in South Korea and Taiwan. In addition, we raised more general concerns related to the purpose and scope of competition policy and implementation in East Asia and the APEC region. More particularized questions and concerns were directed to competition policy in Japan, Canada, Australia, and the United States, especially with respect to either particular areas such as electric power utilities, telecommunications, and intellectual property, or law-related issues such as extraterritorial enforcement and cartel exemptions. During the discussions, two broader, more overarching themes emerged. They are captured in two words: whether and what. The enactment of competition legislation has become a global phenomenon. Competition law has, in effect, become the latest fashion. To be someone, it appears, everyone—including the members of the APEC community—must have a competition statute. For some (particularly the countries of Central and Southeastern Europe as well as the Baltic states) the explanation lies in more than pure fad. To be someone means to be a member of the European “club” and true to the tradition of elite clubs everywhere. Proper dress—in this case competition legislation acceptable to those who run the club—is one of the prerequisites of membership. In this proliferation of competition laws, often scant attention is paid to the most basic questions. For the most part these are quite evident, but they still need to be articulated repeatedly. All too often they are ignored, taken for granted, or simply left unstated. The first question is whether a competition law is needed at all. All but a few advanced industrial states can restate this threshold question by asking whether any type of competition law is appropriate for countries that seek to achieve sustained economic growth. Even when this initial question is answered affirmatively (i.e. that competition policy is important and some sort of competition law would be beneficial), a second question is posed even more rarely: what kind of competition policy and legal regime for its implementation are then appropriate? For many countries, legislators act as if a competition statute without a policy is sufficient. All that seems to be desired is something on the books as well as the additional façade of a nominal enforcement authority in charge. Legislation thus is drafted and enacted with little attention either to the underlying policies that the law might have been designed to establish, or to the capacity of the country’s administrative and legal institutions to enforce effectively. One can approach the questions of whether and what from several perspectives. Economic analysis and comparative legislation come immediately to mind. Some might prefer to use an essentially historical approach. They thus could point to the United States, Germany (and Europe), and Japan as successful examples of industrial countries with the oldest and, by most accounts (excluding Japan), most effective competition laws. The problem with such assertions is that the historical record is quite muddled. With some irony, we become more faithful to the historical experience by debating the issues of whether and what. The principal antitrust statutes were themselves the product of great uncertainty—and, initially in Germany and Japan, imposed regimes. No consensus existed as to the economic need or consequences of the legislation that these countries eventually enacted. The statutes that did emerge after considerable debate were products of compromise, reflecting political reality more than economic analysis. Nor were economic aims the sole, or even predominant, concern. In each case, the equally important if not primary objective was political. That these regimes have become major models is perhaps the greatest irony of all. What remains necessary is a careful assessment of the need for competition policy in both economic and political terms as well as how to design effective legislation to deal with the particular problems of individual countries within the APEC community.
Keywords: Competition (Economics); APEC; Germany; Japan